Nec-1 regulates phenotypic transformation of heat stroke-induced vascular smooth muscle cells by inhibiting RIPK1 - Le Mu; Shujing Xue; Wei Tuo; Xiaomin Wu; Ling Hou; Guanghua Li (International Journal of Hyperthermia)
Objective Cardiovascular injury is a common complication of heat stroke (HS). However, the mechanism underlying vascular smooth muscle cells (VSMCs) following HS remains unclear.Method A rat and VSMCs model was established by simulating high-temperature exposure. Primary VSMC was extracted in vitro, and CCK8 screened the concentration of Nec-1 and detected cell proliferation activity. The expression of α-smooth muscle protein (α-SMA), osteopontin (OPN), receptor-interacting protein kinase 1 (RIPK1), receptor-interacting protein kinase 3 (RIPK3), Bcl-2 and Bax were detected by immunohistochemistry and Western blot.Results The results of in vivo experiments showed that with the prolongation of HS recovery time, α-SMA expression basically decreased and OPN expression increased. Meanwhile, the expression of RIPK1 and RIPK3 was increased, which promoted the occurrence of necroptosis. In vitro results showed that with the extension of HS recovery time, the proliferative viability of VSMCs decreased, the cell morphology changed, and the apoptotic cells increased. The fluorescence results indicate that the expression levels of RIPK1 and PIPK3 in the cells are elevated, accompanied by the typical characteristics of cell necroptosis. Nec-1 restored the decreased cell viability and the high expression of RIPK1 and RIPK3 induced by heat stroke, and improved the occurrence of cell necrotic apoptosis. Nec-1 also restored α-SMA expression, reduced OPN expression, and reversed phenotypic abnormalities of VSMC caused by heat stroke.Conclusion HS induces abnormal phenotypic transformation and necroptosis in VSMCs. Necrostatin-1 can improve necroptosis and maintain the contractile phenotype of VSMCs. This study can provide new insights into cardiovascular damage caused by high temperatures.